PIERWIASTKI ROMANISTYCZNE W PRAWIE SPADKOWYM I STATUTU LITEWSKIEG O - Godek, Sławomir (Zeszyty Prawnicze, 2017)
Roman Elements in Testamentary Regulations of I Lithuanian Statute S u m m a ry Roman law, alongside Lithuanian, Ruthenian, Polish, German and canon law, was one of the many sources of I Lithuanian Statute of 1529. However, it is still not clear how and within what scope the authors of the Lithuanian codification used Roman law. At some point researchers of the subject held the view that the reception of elements of elaborate Roman law could not have possibly happened before II Statute of 1566, from witch such elements were transferred to III Statute of 1588. It seems, however, that a number of Roman elements were already present in I Statute; later on, in the course of the creation of II and III Statute, Roman elements were considerably multiplied and expanded. An interesting subject for research in this connection is testamentary law in I Lithuanian Statute. For instance, Roman law did not allow for wills to be drawn up by minors, slaves, heretics, sons who remained under the authority of their fathers, and by insane persons. The same regulations are to be found in I Statute. It should be emphasized that the reception of Roman legal institution by the Lithuanian codification went as far as to include even exceptions to the general rules; thus, sons were allowed to make wills with respect to their separate property, and insane persons were allowed to make wills when they were in a sound state of mind. I Statute also adopted the Roman legal principle that allowed a testator to freely change his will at any moment in his life. An impact of the Roman legal system can also be seen in I Statute regulations concerning the capacity to be a witness to will making. Under I Statute, persons lacking will-making capacity and women could not be witnesses to will making. It also appears that disinheritance as a legal sanction for hitting or insulting one of the parents was taken over by I Statute from Roman law, perhaps via Byzantine law. An analysis of the regulations of I Statute leads one to the conclusion that the first codification was already under the influence of Roman law, and that the influence was more significant that previously believed. In view of the above observations, further research on the issue may lead to interesting results.